The advertising value of Twitter Ads: a study among Mexican Millennials - Murillo, Enrique; Merino, María; Núñez, Adriana (Review of Business Management, 2016)
Purpose – This study set out to measure the perceived Advertising Value of Twitter ads on a large sample of Mexican Millennials. Design/methodology/approach – An online survey was used to collect data among 630 university students. The hypothesized antecedents of Advertising Value were Informativeness, Entertainment, Irritation and Credibility. The model was estimated using Partial Least Squares. Findings – Results indicate Informativeness and Entertainment were the strongest predictors, with Credibility in third place. In addition, Credibility displayed gender effects: it was significant for female respondents but not for males. Irritation failed to reach statistical significance in most subsamples, suggesting Twitter ads are more acceptable to Millennials than other advertising formats. Originality/value – Millennials tend to dismiss traditional advertising formats. At the same time they are heavy users of Social Networking Sites. This research provides the first empirical estimation of the Ducoffe model of Advertising Value in the microblogging service Twitter, and the first application of this robust model of web advertising to a Latin American sample. Our results have important implications for both regional and global brands targeting Millennials.